Batasan Interaksi Teman Wanita di Kantor dengan Pria Berstatus Menikah Menurut Para Istri - Andu, Christine Purnamasari (representamen, 2020)
AbstractThe research aims to know (1) interaction limit for woman at office with married man according to wives and (2) kinds of the excessive interactions according to wives. This research was used qualitative descriptive method with research location runed at Makassar and Semarang City. Data used for this were primary and secondary data. Total informants are twenty, where ten came from Makassar and another ten from Semarang City. Data collection were done by interviewed with those twenty informants, then being analysed with two theories such as Symbolic Interactionism Theori and Atribution Theori. Research showed that several things a husband and female coworkers should not do like (1) do not chat or discussing things out of work hours or things not related to work, not allowed to go out together, not allowed to do intense communication, not allowed to contact physically like holding hands, etc. (2) excessive interactions were answered 15% for confide, 25% answered contact physically, 25% answered go out together, 10% answered chat in the night late, and 20% answered intense talk as the kinds of excessive interactions according to wives.  Keywords :  Excessive Interaction, Husband, Marriage